Antiangiogenic drugs in the management of ocular diseases: Focus on antivascular endothelial growth factor - Yukio Sassa (Dove Medical Press, 2010)
Yukio Sassa, Yasuaki HataDepartment of Ophthalmology, Graduate School of Medical Sciences, Kyushu University, Fukuoka, JapanAbstract: Age-related macular degeneration (AMD) complications are the leading cause of severe vision loss among the aging population in the many western countries. The introduction of molecular inhibitors of vascular endothelial growth factor (VEGF), such as pegaptanib, ranibizumab, and bevacizumab, as treatments for wet AMD has provided new hope for affected patients. Now we have these treatment options, which have the possibility to improve or maintain visual acuity for patients suffering from AMD. The treatment needs to be optimized and this is in progress. Based on emerging evidence, adopting a variable VEGF inhibitor-dosing strategy guided by visual acuity assessment and optical coherence tomography are now being tried to reduce the frequency of injections. VEGF inhibitors in combination with photodynamic therapy are another way to optimize treatment. Physicians are waiting for new guidelines for the management of AMD and the results of current and upcoming trials systematically addressing these issues will be expected to provide it.Keywords: age-related macular degeneration, VEGF inhibitor, verteporfin, pegaptanib, ranibizumab, bevacizumab